FPGA based SPWM Bridge Inverter - Mohd Nazrin, Md Isa; Muhammad Imran, Ahmad; Sohiful Anuar, Zainol Murad; Mohd Khairuddin, Md Arshad (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php